HR Transformation in China under the Influence of Organizational Culture - Gao, Yi (2017)
In order to cope with the fierce competition among companies, HR practitioners in China begin to adopt western HR practices and change their roles from administrative roles to strategic roles. However, the effectiveness of their roles is questioned by researchers. Besides, as organizational culture has become one of the key factors that influence the achievement of an organization, this research aims to examine the transformation of HR roles under the influence of organizational culture. As there are lots of studies focus on the HR roles in developed countries, it leaves a gap to investigate in developing countries. This study aims to fill this gap and find out what is the dominant HR role in China under the background of HR transformation and what are the organizational culture factors that influence the performance of HR roles, and what influence them being strategic. The data in this research is obtained through questionnaire, which is later analyzed using a statistical tool, SPSS. The total number of respondents is 118 employees, who work in different types of companies with different roles. Mean and standard deviation are checked to figure out the dominant HR role in China. The Pearson’s correlation coefficient examines the correlation between variable. Hierarchical multiple regressions are used twice. The first regression is used to understand the impact of organizational culture types on HR roles. The second regression is used to understand the impact of organizational culture dimensions on HR roles. The result shows three main features. First, the dominant HR role in China is administrative expert. Second, the clan culture contributes most to the performance of all HR roles. Third, strategic emphases are the contributor to the performance of administrative expert and change agent. Management of employee contributes most to the performance of employee champion. Both dominant characteristics and strategic emphases are the contributors to the performance of strategic partner, with strategic emphases contribute more.